Evolutionary games in natural, social, and virtual worlds - Friedman, Daniel 1947-; Sinervo, Barry (Oxford University Press, 2016)
Authors Daniel Friedman and Barry Sinervo show how to use theoretical developments in evolutionary game theory to build useful models describing parts of the worlds we live in - the natural world of biology, the social world of politics, economics, etc., and the virtual world that is emerging from our connected electronic devices.